The consequence of the first attack of acute rheumatic fever with subclinical carditis - Heiba, Doaa Abdel-Moez (International Journal Of Community Medicine And Public Health, 2019)
Background: Immune mediated damage of RF occurs most prominently in the heart, joints, brain, skin and subcutaneous tissues, however RF leaves no lasting damage to the brain, joint or skin, it is the leading cause of acquired heart disease in children and adolescents worldwide, therefore carditis is the most important manifestation of RF. Echocardiography along with color; Doppler imaging is now worldwide used for early detection of cardiac involvement even in the absence of clinical evidence, which in this case is called subclinical carditis (SCC) and was reported to cause similar consequences to clinically evident carditis. Methods: A retrospective study carried out on 35 patients already diagnosed to have RF and subclinical RHD and attending the cardiology clinic at Alexandria University Children’s Hospital (AUCH) from December 2015 to November 2016. Data collected from patients' files and then appropriately updated during subsequent follow-up visits. Results: 35 children already diagnosed to have RF and subclinical RHD were included in the current study, 22 patients (66.6%) improved completely with no residual cardiac lesion, 10 patients (30.3%) had persistent lesion and one patient (3.1%) had worsened condition. Conclusions: The most important predictors of poor prognosis according to the current study were recurrence and lack of regular compliance to long acting penicillin (LAP). Furthermore the outcome was not influenced by the treatment given in the initial attack.